Use of Vermicompost for the Removal of Toxic Metal Ions of Synthetic Aqueous Solutions and Real Aqueous Waste - Barbosa, Luane Patricia Guedes; de Freitas, Tácila Oliveira Pinto; Pereira, Madson de Godoi (Eclética Química, 2018)
Samples of vermicompost were used to decontaminate aqueous media containing Cd2+, Cu2+, Mn2+, Ni2+, Pb2+ and/or Zn2+ at concentration up to 10X higher than the limits of National Council of the Environment (Resolution 430/2011). For this purpose, 50.00 mL of synthetic solutions and wastewater from a chemical laboratory were stirred with dried vermicompost (~10.0000 g), in natura or with diameter ≤ 0.053 mm. Aqueous media were treated with vermicompost, either at rest (24, 48, 72, and/or 96 h) or under mechanical agitation (2, 4, 6, 8, and/or 10 h). All elements were spectrometrically determined in the different supernatants. In the synthetic solutions, except for Mn2+and Zn2+, all cations were undetectable (concentrations lower than the legal limits), when in natura vermicompost was used. After treating synthetic solutions with sieved vermicompost, Cd2+, Cu2+, Ni2+, Pb2+ e Zn2+ concentrations were undetectable, while Mn2+ concentrations were too close to the legal limits. In the wastewater, Cd2+and Pb2+ concentrations, which were 1.5 and 3.8X higher than the legal limits, respectively, were undetectable after treatment with vermicompost in natura. Besides its efficiency of retaining the evaluated metallic cations, vermicompost was able to increase the aqueous media pH from 0.9 to 6.0 ± 0.5.